A preliminary analysis of land use change and its impacts on groundwater resources in Balamban, Cebu, Philippines using GIS - Bagarinao, Ricardo T. (2003)
Groundwater is potentially affected when land use changes due to agricultural and industrial developments. As there are many cases of groundwater degradation due to changing land use patterns throughout the world, a preliminary examination of the interrelationship between land use change and groundwater resource viability is in order. The analysis could be enchanced through the use of geographic information system (GIS).

A computer-assisted map overlay technique was used to analyze the changes in land use pattern in 1980, 1990, and 2000 in Balamban, Cebu. The same technique was utilized to identify the impact zones and analyze the potential impacts associated with land use change.

The overlays revealed 20 patterns of land use change in the study site. The change from grassland to forest showed the highest areal change (50. 55 km²) from 1980 to 2000. This is folowed by the change from grassland to agricultural (49. 34 km²) and from agricultural to built-up (44. 69 km²). Integrating the result with land permeability information showed that major land conversion took place within permeable to highly permeable areas that were overlying shallow and deep well areas, the two major sources of water in the municipality. Consequently, the conversion could potentially affect these sources by contaminating groundwater and depleting the stock. Contamination may result from agricultural, domestic, and industrial/commercial activities while depletion may result from changing highly permeable areas to built-up areas that would potentially reduce groundwater recharge. Depletion would also result from increasing water extraction as demand rises with development. However, further analysis of the links between land use change and potential impacts is necessary for results to be conclusive.